The effect adding layer manure in ration as alternative feed on pig production - Sinaga, Saulan; Silalahi, Marsudi (Indonesian Journal of Animal and Veterinary Sciences, 2002)
An experiment had been conducted to find out the effect of layer manure in the ration pig. Twenty four pig were randomized into 24 individual pens. Completely Randomized Design was used in this experiment; treatments consist of four levels of layer manure (0; 5; 10 and 15%), each treatment was replicated six times. The result indicated that up to 5% layer manure add to the starter-grower diet can be fed without any significant effect. Â  Key words: Layer manure, starter-grower period